Reduction of accidents at motorway exits (Journal of Industrial and Mechanical Engineering, 2025)
Traffic congestion situations at the entrances and exits of highways in various cities represent a serious and increasingly intolerable problem for users in their daily activities. These congestions, often unnoticed at the beginning, arise from structural and construction deficiencies in highways, as well as from the lack of adequate signage that anticipates and provides information in real time. The lack of planning and adequate updating generates inefficient designs, manifested in a significant increase in the risk of accidents, causing irreparable damage to the life and health of users. In addition, these congestions result in substantial delays that affect productivity and quality of life. The time lost in traffic could be spent on more productive and personal activities. The situation also leads to excessive fuel consumption, raising operating costs and increasing the carbon footprint, which contributes negatively to environmental deterioration. If we recognize the possibility of minimizing this situation through improvements in infrastructure, highway design and the implementation of real-time smart signage, we will be able to not only improve road safety, but also optimize the use of time and resources, promoting more efficient and sustainable mobility.
Keywords: highway safety, highway limitations, highway accidents, highway design